Self-efficacy and women sustainable entrepreneurship in an emerging economy: Role of bricolage and attitude in the era of open innovation - Jeevan Jyoti; Ganesh Dash; Asha Rani; Sumeet Kour; Layla Khaled Nasser (Journal of Open Innovation: Technology, Market and Complexity, 2025)
Women entrepreneurs play a vital role in sustainable entrepreneurship by balancing societal, ecological, and economic sustainability. Building upon an emerging economy context, this study examines the effect of selected factors on sustainable entrepreneurship in the context of women entrepreneurs. It explores the role of entrepreneurial bricolage between self-efficacy and sustainable entrepreneurship. Further, the role of attitude towards business sustainability as a strengthening (moderator) variable between bricolage and sustainable entrepreneurship has also been evaluated. Three hundred female entrepreneurs from an emerging economy were approached. Exploratory and confirmatory factor analyses have been used to validate the data. The findings revealed that entrepreneurial bricolage mediates self-efficacy and sustainable entrepreneurship. This suggests that women entrepreneurs with self-efficacy are more likely to engage in creative and resourceful problem-solving, which fosters sustainable business practices. Further, attitude towards business sustainability moderates the relationship between entrepreneurial bricolage and sustainable entrepreneurship. This implies that women entrepreneurs prioritizing sustainability are more effective in utilizing bricolage to achieve sustainable outcomes. The present study contributes to the literature by identifying bricolage and attitude towards business sustainability as important intervening and extraneous variables between self-efficacy and sustainable entrepreneurship. Further, the micro and macro-level implications in an emerging economy context have also been discussed.